2021
DOI: 10.1021/acs.inorgchem.1c02905
|View full text |Cite
|
Sign up to set email alerts
|

Approach toward Iron(II) Coordination Polymers Based on Chain Motifs with Thiolate or Mixed Thiolate/Carboxylate Bridges: Structures and Magnetic Properties

Abstract: The search for iron–sulfur-based coordination polymers (CPs) has become an attractive field in recent years. Here we demonstrate how it is possible to synthesize new iron–sulfur-based CPs by solvothermal reactions of [CpFe­(CO)2]2 (Cp = cyclopentadienyl) with two positional isomeric ligands 6-mercaptonicotinic acid (6-H2mna) and 2-mercaptoisonicotinic acid (2-H2mina) in different mixed-solvent systems. The reactions afforded, in moderate yields, a variety of desired CPs, namely, [Fe­(6-Hmna)2] (1), [Fe3(6-Hmna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Although in both cases inorganic chains are built from edge-sharing octahedra, the way they are connected also differs, with the formation of a straight chain vs. a helical one in {Fe(DSBDC)} and Fe 2 (DSBDC)(DMF) 2 , respectively, giving rise to shorter Fe–Fe distances in the CPO-27 analogue (3.19 vs. 3.55 Å). More interestingly, the coordination environment of Fe and the chain-like motif in {Fe(DSBDC)} are nearly identical to those found in the iron-thiolate-carboxylate 1-D coordination polymer [Fe(6-Hmna) 2 ] (6-H 2 mna = 6-mercaptonicotinic acid) reported by Du et al 22 This compound is indeed built of similar edge-sharing FeS 4 O 2 polyhedra, with slightly longer Fe–S and Fe–O bond distances (see Table 2), and thus, longer Fe⋯Fe distances (3.83 vs. 3.55 Å). This fact could be easily rationalized considering that Fe adopts a +2 oxidation state in [Fe(6-Hmna) 2 ], which possesses a larger ionic radius than Fe( iii ).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Although in both cases inorganic chains are built from edge-sharing octahedra, the way they are connected also differs, with the formation of a straight chain vs. a helical one in {Fe(DSBDC)} and Fe 2 (DSBDC)(DMF) 2 , respectively, giving rise to shorter Fe–Fe distances in the CPO-27 analogue (3.19 vs. 3.55 Å). More interestingly, the coordination environment of Fe and the chain-like motif in {Fe(DSBDC)} are nearly identical to those found in the iron-thiolate-carboxylate 1-D coordination polymer [Fe(6-Hmna) 2 ] (6-H 2 mna = 6-mercaptonicotinic acid) reported by Du et al 22 This compound is indeed built of similar edge-sharing FeS 4 O 2 polyhedra, with slightly longer Fe–S and Fe–O bond distances (see Table 2), and thus, longer Fe⋯Fe distances (3.83 vs. 3.55 Å). This fact could be easily rationalized considering that Fe adopts a +2 oxidation state in [Fe(6-Hmna) 2 ], which possesses a larger ionic radius than Fe( iii ).…”
Section: Resultssupporting
confidence: 71%
“…The reactivity of H 4 DSBDC and related ligands with a large variety of cations has been already explored, notably by the team of Z. Xu. In line with the hard and so acid and base (HSAB) theory, 20 it was found that networks comprising M(I) (M = Ag) and M(II) (M = Fe, Co, Ni, Cu, Pb) cations rely on M-S (and M-O) bonds, [21][22][23] while those based on M(III) (M = Al, Eu) and M(IV) (M = Zr) cations are based exclusively on M-O bonds. 21,[24][25][26][27][28] Nevertheless, studies on molecular complexes derived from thiosalicylic acid reveal that the formation of M-S bonds with high-charge cations (e.g.…”
Section: Introductionmentioning
confidence: 79%
“…A step-like behavior is also found in the M­(H) hysteresis loop near the applied low field region (see the step in black M­(H) curve near the zero-field). Therefore, the above features found in M­(T) [the divergence observed in ZFC and FC curves] and M­(H) [step-like] are consistent with a weak canted spin structure that is strongly affected by DC applied magnetic fields. , A large coercive H C field of 10 kOe and remnant magnetization (M r ) of 1.91 Nβ are found after the sample magnetization. The high H C field are found in frustrated magnetic systems with noncollinear spin structures, behaving as hard magnets.…”
Section: Resultssupporting
confidence: 62%
“…Transition metals have additional d-orbitals available for bonding with linkers, therefore transition metal-based ISBU MOFs exerted better stability normally and have been widely studied. [73][74][75][76][77][78][79] He and his colleagues 76 synthesized a series of 1D Fe(II)-MOF characteristic of excellent thermal stability. Taking the Fe(II)-MOF-1 [Fe(6-H 2 MNA) 2 , 6-H 2 MNA ¼ 6-mercaptonicotinic acid] for representation, it was produced by the reaction of [CpFe(CO) 2 , Cp ¼ cyclopentadienyl] and 6-H 2 MNA at 160 C for 2 days in a mixed solvent of toluene and water.…”
Section: Isbu Mofs Constituted Of Metal(ii) Central Ionsmentioning
confidence: 99%